Implementation of Setting and Infrastructure (SI) At Politeknik Negeri Medan Based on UI GreenMetric Guideline 2023 - Dary, Rhini Wulan; Subhan, Muhammad Ari; Sitompul, Mizanuddin; Nofriadi; Carlo, Nasfryzal (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Campus is the right place to promote the concept of sustainable development to the academic community and the surrounding community. The application of the green campus concept is a sustainable effort to reduce carbon that occurs on the Medan State Polytechnic campus. Based on the UI GreenMetric Guideline 2023, we will find out how much scoring from the existing conditions achieved for the setting and infrastructure (SI) category from the maximum scoring of 15% of the total. By knowing the scoring of the existing conditions, the researcher seeks to be able to increase the scoring of the SI indicator based on the UI GreenMetric Guideline 2023 which will be outlined in the final landscape of Medan State Polytechnic to get the maximum score of the SI indicator based on the UI GreenMetric Guideline 2023. The method used is quantitative using primary data and secondary data. Primary data was obtained by conducting surveys while secondary data was obtained from the Medan State Polytechnic agency. From the results of the scoring calculation for the setting and infrastructure (SI) category, the Politeknik Negeri Medan campus received a score of 440 out of 1500 points or 29.33%. For efforts to increase scoring, the maximum value is 575 points out of 1500 points. Only 9% can be maximized for additional scoring that can be done on the Politeknik Negeri Medan. So that the final score obtained is 38.33%. The researcher hopes that the research can be useful for Politeknik Negeri Medan as a sustainable effort to implement the green campus concept at Politeknik Negeri Medan.